2022
DOI: 10.1183/23120541.00650-2021
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmaceutical interventions to prevent viral respiratory infection in community settings: an umbrella review

Abstract: BackgroundRespiratory viruses pose an important public health threat to most communities. Non-pharmaceutical interventions (NPIs) such as masks, hand hygiene, or physical distancing among others are believed to play an important role in reducing transmission of respiratory viruses. In this umbrella review, we summarize the evidence of the effectiveness of NPIs for the prevention of respiratory virus transmission in the community setting.ObservationsA systematic search of PubMed, Embase, Medline, and Cochrane r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
5
0
1
Order By: Relevance
“…However, given the delay of vaccine eligibility for children under 5 years, in March 2021, the CDC expanded their recommendations for mask wearing to include individuals aged 2 years and older (CDC, 2021), particularly within the context of congregate care settings (e.g., childcare programs). Further, following the onset of the COVID‐19 pandemic, research has supported mask wearing to reduce the spread of other respiratory illnesses such as influenza (flu) and respiratory syncytial virus (RSV; Chaabna et al., 2021; Zhao et al., 2022), especially during times of the year and in settings for which transmission is more likely (i.e., winter and high travel seasons and school and childcare settings; CDC, 2022). Thus, it was at the time of this study, and continues to be, important to develop and evaluate procedures for increasing mask wearing in young children.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the delay of vaccine eligibility for children under 5 years, in March 2021, the CDC expanded their recommendations for mask wearing to include individuals aged 2 years and older (CDC, 2021), particularly within the context of congregate care settings (e.g., childcare programs). Further, following the onset of the COVID‐19 pandemic, research has supported mask wearing to reduce the spread of other respiratory illnesses such as influenza (flu) and respiratory syncytial virus (RSV; Chaabna et al., 2021; Zhao et al., 2022), especially during times of the year and in settings for which transmission is more likely (i.e., winter and high travel seasons and school and childcare settings; CDC, 2022). Thus, it was at the time of this study, and continues to be, important to develop and evaluate procedures for increasing mask wearing in young children.…”
Section: Introductionmentioning
confidence: 99%
“…Among environmental pathogens, viruses cannot replicate without infecting host cells, however most bacteria and fungi can survive and grow on various materials depending on the environmental conditions (Park et al, 2022). Bacteria and fungi are widely present on the surface of the materials used in our daily lives such as currency notes and in public transportation systems (Jefferson et al, 2020;Zhao et al, 2022). Although a few studies reported bacterial or viral contamination on masks in experimental and clinical settings, there is a need to study the characteristics of the various microbes that are present on face masks used daily in our day-to-day activities (Park et al, 2022;Gonçalves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wearing masks may be one solution: Ko and colleagues were unable to estimate the effect of masks or hand hygiene in their study, but these appear to reduce the transmission of respiratory viruses. 7 Should we encourage those with chronic respiratory diseases to wear masks during winter and when they are likely to be exposed to viruses? Healthcare workers should consider wearing masks when treating respiratory patients, and of course should practice careful hand hygiene.…”
mentioning
confidence: 99%
“…What other measures are useful that could be continued after the pandemic is over and what alternative approaches might work? Wearing masks may be one solution: Ko and colleagues were unable to estimate the effect of masks or hand hygiene in their study, but these appear to reduce the transmission of respiratory viruses 7 . Should we encourage those with chronic respiratory diseases to wear masks during winter and when they are likely to be exposed to viruses?…”
mentioning
confidence: 99%